Peningkatan Pemahaman Pelaporan Pajak Penghasilan Manajemen Yayasan Pengelola Jurnal Elektronik: Peningkatan Pemahaman Pelaporan Pajak Penghasilan Manajemen Yayasan Pengelola Jurnal Elektronik - anggono anggono; Siti Aisyah Nasution; Sauh Hwee Teng; Siti Dini; Puji Harianti; Tar wiyah; Ahmad Saputra; Ari Irawan; Melinda Siregar; Corinna Wongsosudono (Jurnal Mitra Prima, 2026)
This community service activity was conducted to improve tax understanding through socialization in the form of training at Yayasan Literasi Emas Nusantara. The main issue addressed by the foundation was that many members had not yet comprehensively understood tax obligations, including tax reporting procedures. The activity was carried out using lecture-based instruction, simulations, and interactive question-and-answer sessions. To measure the improvement in participants’ understanding, pre-tests and post-tests were administered with a success indicator of an average score of 60. The pre-test results showed an average score of 43, while the post-test score increased to 62, exceeding the predetermined indicator. These results indicate that tax socialization and training effectively improved participants’ tax understanding. Furthermore, adequate tax knowledge can enhance taxpayers’ compliance and independence in reporting personal taxes. However, the limitation of this activity was the relatively short training duration; therefore, follow-up training with sufficient time allocation is recommended for deeper material comprehension.